Spinning wheel from the late 1800s-early 1900s, originally owned by Mrs. Gaudon’s great-grandmother and still in use - Tourout, Geraldine (1980)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « The Folk Materials in my Parents Home ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "The Folk Materials in my Parents Home".